TANTANGAN PENDIDIKAN MASA KINI DALAM PERSPEKTIF ISLAM DI ERA GLOBALISASI - Yani Novita Sari; Zifa Yeni; Bismi Afia; Meri Yessari; Alpan Suri; Azizah Nurazila; Hendrizal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Globalization has had a significant impact on education, including Islamic education, with challenges such as the digitalization of learning, the influence of global culture, and changes in 21st century skills needs. This research aims to analyze these challenges from an Islamic perspective, identifying strategies to maintain Islamic values ​​while facing the flow of globalization. The method used is qualitative library research with descriptive-analytic analysis of literature related to Islamic education and globalization. Islamic education is faced with great challenges in maintaining religious identity and moral values ​​amidst cultural and technological influences that conflict with Islamic teachings. For this reason, Islamic education needs to play an active role in maintaining Islamic identity, affirming understanding of Islamic values, and forming the character of students who are intellectually intelligent and have noble morals. Islamic education must be responsive to changing times, including technological advances and the challenges of multiculturalism, by integrating digital literacy and inclusive education. The basic principles of Islamic education such as piety, justice, morality and knowledge must be maintained in order to create individuals who are balanced between worldly and spiritual aspects. The strategies needed include revitalizing the role of education, curriculum innovation, as well as strengthening digital literacy and character education based on Islamic values. In this case, Islamic education must be able to adapt to current developments without sacrificing the essence of Islamic teachings, creating a generation that is intellectually competent and strong in moral and spiritual integrity.